2016
DOI: 10.1111/maq.12309
|View full text |Cite
|
Sign up to set email alerts
|

Publically Misfitting: Extreme Weight and the Everyday Production and Reinforcement of Felt Stigma

Abstract: Living with extreme weight in the United States is associated with discrimination and self‐stigma, creating structural exclusions, embodied stress, and undermining health and wellbeing. Here we combine ethnographic interviews and surveys from those with experiences of living with extreme weight to better explain how this vulnerability is created and reinforced by public cues, both physical (e.g., seatbelts) and social (the reactions of strangers). “Misfitting” is a major theme in interviews, as is the need to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 64 publications
4
48
0
2
Order By: Relevance
“…Nichter, 2000;Taylor, 2016;Trainer, Brewis, Williams, & Rosales Chavez, 2015), especially in light of the documented stigma associated with "fat" in the US (e.g. Brewis, Trainer, Han, & Wutich, 2015;Greenhalgh, 2015). As such, face-to-face interactions require more than mere acknowledgement of a speaker's fat talk utterance.…”
Section: Finding 2: the Two Methods Produce Different Frequencies Omentioning
confidence: 99%
“…Nichter, 2000;Taylor, 2016;Trainer, Brewis, Williams, & Rosales Chavez, 2015), especially in light of the documented stigma associated with "fat" in the US (e.g. Brewis, Trainer, Han, & Wutich, 2015;Greenhalgh, 2015). As such, face-to-face interactions require more than mere acknowledgement of a speaker's fat talk utterance.…”
Section: Finding 2: the Two Methods Produce Different Frequencies Omentioning
confidence: 99%
“…Besides suffering stigmatization from relatives, coworkers, health-care professionals, and strangers, our participants shared experiencing uncomfortable situations in public spaces, which involved feeling -misfit‖ in some places. In the study of Brewis et al (2016), the participants shared ideas that were similar to those reported by our participants: "It became more weight-related when was harder for me to get around and harder for me to find a chair that would fit my behind… I also know if I broke something I'd feel bad." In another qualitative study, participants reported that facing this kind of stigma made them feel deviant from what is acceptable in our current society (Lewis et al 2011).…”
Section: Discussionsupporting
confidence: 58%
“…Weight discrimination and obesity stigmatization are important issues to be studied since they can be partly responsible for health problems immediately attributed to obesity (Maclean et al, 2009). Although some research has investigated weight-related discriminations in social interactions Brewis et al, 2011), healthcare professionals (Brown, 2007), media (Malterud and Ulriksen, 2010), public health actions (Lewis et al, 2010), everyday social relationships (Brewis et al, 2011), and social spaces (Brewis et al, 2016), only a limited number has qualitatively examined how such prejudices and body image of obese people influence emotional and physical well-being. Therefore, we aimed to investigate, qualitatively, obese women's perceptions of their own bodies and their experiences with weight-related discriminations, and how these experiences affect their wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…Fat bodies are highly stigmatised – especially those who are at the most extreme end of the spectrum (Brewis et al . , Carr and Jaffe , Lupton ).…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Despite the growth of these discourses which seek to combat fat stigma and ‘fat shaming’ – there still remains a strong culture of stigma and shame particularly among people who carry an extreme amount of weight (Brewis et al . ) and among bariatric patients (Hansen and Dye , Raves et al . ).…”
Section: Conceptual Backgroundmentioning
confidence: 99%